Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine the quadratic equation that best fits the given table of values, we assume that the relationship between \(y\) and \(x\) can be described by a quadratic equation of the form:
[tex]\[ y = ax^2 + bx + c \][/tex]
We are given the following data points:
[tex]\[ \begin{array}{c|c} x & y \\ \hline 0 & 4 \\ 1 & 7 \\ 2 & 16 \\ 3 & 31 \\ 4 & 52 \\ \end{array} \][/tex]
We can substitute these points into the quadratic equation to formulate a system of linear equations.
### Step-by-Step Solution
1. Substitute \(x = 0\) and \(y = 4\) into the equation:
[tex]\[ 4 = a(0)^2 + b(0) + c \][/tex]
[tex]\[ 4 = c \][/tex]
So, \( c = 4 \).
2. Substitute \(x = 1\) and \(y = 7\) into the equation:
[tex]\[ 7 = a(1)^2 + b(1) + c \][/tex]
Since \( c = 4 \):
[tex]\[ 7 = a + b + 4 \][/tex]
[tex]\[ 7 - 4 = a + b \][/tex]
[tex]\[ 3 = a + b \][/tex]
3. Substitute \(x = 2\) and \(y = 16\) into the equation:
[tex]\[ 16 = a(2)^2 + b(2) + c \][/tex]
Since \( c = 4 \):
[tex]\[ 16 = 4a + 2b + 4 \][/tex]
[tex]\[ 16 - 4 = 4a + 2b \][/tex]
[tex]\[ 12 = 4a + 2b \][/tex]
[tex]\[ 6 = 2a + b \][/tex]
4. We now have two equations from steps 2 and 3:
[tex]\[ 3 = a + b \][/tex]
[tex]\[ 6 = 2a + b \][/tex]
To solve for \(a\) and \(b\), we can subtract the first equation from the second:
[tex]\[ (2a + b) - (a + b) = 6 - 3 \][/tex]
Simplifying, we get:
[tex]\[ a = 3 \][/tex]
Substituting \(a = 3\) back into the first equation:
[tex]\[ 3 = 3 + b \][/tex]
[tex]\[ b = 0 \][/tex]
### Conclusion
Thus, we have found the coefficients:
[tex]\[ a = 3 \][/tex]
[tex]\[ b = 0 \][/tex]
[tex]\[ c = 4 \][/tex]
The quadratic equation describing the relationship between \( y \) and \( x \) is:
[tex]\[ y = 3x^2 + 0x + 4 \][/tex]
[tex]\[ y = 3x^2 + 4 \][/tex]
This quadratic equation fits the given table of values perfectly.
[tex]\[ y = ax^2 + bx + c \][/tex]
We are given the following data points:
[tex]\[ \begin{array}{c|c} x & y \\ \hline 0 & 4 \\ 1 & 7 \\ 2 & 16 \\ 3 & 31 \\ 4 & 52 \\ \end{array} \][/tex]
We can substitute these points into the quadratic equation to formulate a system of linear equations.
### Step-by-Step Solution
1. Substitute \(x = 0\) and \(y = 4\) into the equation:
[tex]\[ 4 = a(0)^2 + b(0) + c \][/tex]
[tex]\[ 4 = c \][/tex]
So, \( c = 4 \).
2. Substitute \(x = 1\) and \(y = 7\) into the equation:
[tex]\[ 7 = a(1)^2 + b(1) + c \][/tex]
Since \( c = 4 \):
[tex]\[ 7 = a + b + 4 \][/tex]
[tex]\[ 7 - 4 = a + b \][/tex]
[tex]\[ 3 = a + b \][/tex]
3. Substitute \(x = 2\) and \(y = 16\) into the equation:
[tex]\[ 16 = a(2)^2 + b(2) + c \][/tex]
Since \( c = 4 \):
[tex]\[ 16 = 4a + 2b + 4 \][/tex]
[tex]\[ 16 - 4 = 4a + 2b \][/tex]
[tex]\[ 12 = 4a + 2b \][/tex]
[tex]\[ 6 = 2a + b \][/tex]
4. We now have two equations from steps 2 and 3:
[tex]\[ 3 = a + b \][/tex]
[tex]\[ 6 = 2a + b \][/tex]
To solve for \(a\) and \(b\), we can subtract the first equation from the second:
[tex]\[ (2a + b) - (a + b) = 6 - 3 \][/tex]
Simplifying, we get:
[tex]\[ a = 3 \][/tex]
Substituting \(a = 3\) back into the first equation:
[tex]\[ 3 = 3 + b \][/tex]
[tex]\[ b = 0 \][/tex]
### Conclusion
Thus, we have found the coefficients:
[tex]\[ a = 3 \][/tex]
[tex]\[ b = 0 \][/tex]
[tex]\[ c = 4 \][/tex]
The quadratic equation describing the relationship between \( y \) and \( x \) is:
[tex]\[ y = 3x^2 + 0x + 4 \][/tex]
[tex]\[ y = 3x^2 + 4 \][/tex]
This quadratic equation fits the given table of values perfectly.
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.